A hybrid in situ and on-screen survey to monitor gully erosion across the European Union - Pasquale Borrelli; Francis Matthews; Christine Alewell; Konstantinos Kaffas; Jean Poesen; Philipp Saggau; Remus Prăvălie; Matthias Vanmaercke; Panos Panagos (Scientific Data)
Abstract After the successful mapping of gully erosion channels in the 2018 Eurostat Land Use/Cover Area Frame (topsoil) statistical survey (LUCAS, n = 24,759 locations), the methodology was further expanded across the full LUCAS 2022 survey (n = 399,591 locations). This expert-based assessment identifies the presence or absence of gully erosion forms at each LUCAS location. Its goal is to improve understanding of gully erosion geography in the EU and develop forecasting methods to support soil health indicators proposed by the new Directive on Soil Monitoring and Resilience (COM(2023)416) and Common Agricultural Policy monitoring. Here, we present the findings of our analysis which led to the development and validation of the LUCAS Gully Erosion Model (GE-LUCAS v1.1), a pan-European inventory of gully erosion channels comprising 3,116 locations (~0.8% of all monitored locations) affected by gully erosion throughout the European Union. We further present gully erosion patterns and provide insights on how GE-LUCAS v1.1 inventory can be used to estimate the probability of gully occurrence in areas beyond the monitored locations.